Entrepreneurship in the Agricultural Sector: A Literature Review and Future Research Opportunities. (January 2018) - Fitz-Koch, Sarah; Nordqvist, Mattias; Carter, Sara; Hunter, Erik
Heeding calls for contextualizing entrepreneurship research and for greater attention to the role of sector in entrepreneurship research, we conduct a systematic literature review of extant research in agricultural entrepreneurship. Recent and rapid vertical integration and rationalization within the agricultural sector provides a dynamic setting for scholars to investigate entrepreneurship theory and practice. We identify three key contextual dimensions of the agricultural sector: identity, family, and institutions, which provide promising opportunities for future research and the potential to contribute to and extend current theoretical and empirical analyses of entrepreneurship research.